Young’s Inequality for Convolutions in Morrey-Type Spaces - Burenkov, Victor Ivanovich; Tararykova, Tamara Vasil’evna (Eurasian Mathematical Journal, 2016)
An analogue of the classical Young’s inequality for convolutions of functions is proved in the case of the general global Morrey-type spaces. The form of this analogue is different from Young’s inequality for convolutions in the case of the Lebesgue spaces.